Synergistic effect of antiangiogenic nanotherapy combined with methotrexate in the treatment of experimental inflammatory arthritis - Zhou, Hui-fang (2010)
AIM: This study examines the effect of combining the antiangiogenic effect of α(v)β(3)-targeted fumagillin nanoparticles with the conventional antirheumatic drug methotrexate for the treatment of inflammatory arthritis. METHOD: Arthritis was induced in mice by K/BxN serum transfer, and disease activity was monitored by clinical score and change in ankle thickness. Groups of mice received nanoparticles or methotrexate as single therapy or nanoparticles and methotrexate as combination therapy. RESULTS: We found that animals treated with a pulse dose of fumagillin nanoparticles followed by methotrexate had significantly improved and sustained clinical response compared with those treated with either agent alone. Histological analysis confirmed a significant decrease in inflammatory cell influx, bone erosions, cartilage damage and angiogenesis with the combination therapy. CONCLUSION: Analysis of plasma cytokine levels suggests that fumagillin nanoparticles enhanced the systemic anti-inflammatory effects of methotrexate. Antiangiogenic nanotherapy may represent a promising approach for the treatment of inflammatory arthritis when combined with a conventional antirheumatic drug.